2015 ASEE Annual Conference and Exposition Proceedings
DOI: 10.18260/p.23678
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Latino/a Adolescents' Engineering Self-efficacy and Perceptions of Engineering After Addressing Authentic Engineering Design Challenges

Abstract: Dustin Drake is currently a graduate student at Utah State University. While being raised in a small town in southern Utah, Dustin had very few experiences with regards to diversity in his community. As a young adult, he had the opportunity to live in Guadalajara, Mexico, for a few years. He immersed himself in this new culture, learned the language, and loved experiencing new ways of seeing the world. Through this foreign experience, Dustin recognized a shift in his identity. These experiences also led him to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…Implied through the lack of papers that focus on disability as an identity, these findings indicate that within engineering education, the experiences of the disabled community, of disabled students, and of disabled engineers are not yet part of our concepts of diversity and inclusion. With even the 2015 Best Diversity Paper Awards limited to discussing disability through design projects, 14 the need to face the challenge of starting conversations about disability remains pressing.…”
Section: Discussionmentioning
confidence: 99%
“…Implied through the lack of papers that focus on disability as an identity, these findings indicate that within engineering education, the experiences of the disabled community, of disabled students, and of disabled engineers are not yet part of our concepts of diversity and inclusion. With even the 2015 Best Diversity Paper Awards limited to discussing disability through design projects, 14 the need to face the challenge of starting conversations about disability remains pressing.…”
Section: Discussionmentioning
confidence: 99%
“…35 In this sense, engineering can be described as a microculture that encompasses human phenomena related to learned behavior patterns distinctive of a culture such as the norms, beliefs, expectations, or conventional actions. According to Godfrey and Parker, in order to move toward a cultural change, we must look into the collective "values, beliefs and assumptions which underpin the culture of engineering education at the disciplinary, departmental, or institutional level" (p.18).…”
Section: Discussionmentioning
confidence: 99%
“…48 For instance, in one study, researchers first identified the assets Latina/o high school students brought, then connected these to community-engaged design projects. 48,49 Such approaches help develop students' self-efficacy and make engineering seem more relevant and more connected to their lives, 50 thus better supporting underrepresented minority students to learn. 51,52 Asset-based approaches have been shown to support low income, first-generation college attendees, revealing they bring assets such as the ability to define and solve problems related to limited financial means, and having empathy for marginalized communities.…”
Section: Developing Professional Engineering Identitymentioning
confidence: 99%